A single burr hole approach for direct transverse sinus cannulation for the treatment of a dural arteriovenous fistula. (15th January 2014) - Caplan, Justin M; Kaminsky, Ian; Gailloud, Philippe; Huang, Judy
Abstract : A 55-year-old woman with a symptomatic Borden II/Cognard IIa+b transverse sinus dural arteriovenous fistula underwent an attempted percutaneous transvenous embolization which was ultimately not possible given the fistula anatomy. She then underwent a partial percutaneous transarterial embolization but the fistula recurred. Given the failed percutaneous interventions, the patient underwent a combined open surgical/transvenous embolization using neuronavigation and a single burr hole craniectomy. She has remained symptom free for 3 months. This case report illustrates the feasibility of combining minimally invasive open surgical access to allow for direct venous cannulation for endovascular embolization of a dural arteriovenous fistula when traditional percutaneous methods are not an option.